Study on water quality based on physicochemical parameters and distribution of waste in the waters of Kelapa Dua Island - Fittrie Meyllianawaty Pratiwy; Titin Herawati; Zahidah Hasan; Yuli Andriani; Thallita Nasywa Faddilah; Tiara Nurul Nabila (Depik, 2024)
Kepulauan seribu archipelago is home to Kelapa Dua Island, a potential marine tourism destination and habitat for diverse marine life. The survival of marine biota hinges on suitable physical and chemical water parameters, encompassing temperature, pH, salinity, and dissolved oxygen (DO). This study aims to evaluate water quality and litter distribution on Kelapa Dua Island within Kepualauan Seribu National Park. Results reveal that the water quality largely aligns with established standards; however, specific points surpass limits, notably lower salinity at stasion 3 (26%o), and higher pH at station 2 (9.35). Despite meeting quality standards, the island's status as a populated area and tourist destination raises concerns about potential alterations to water quality. Furthermore, observations on litter distribution indicate a status categorized as B (0-4/m) and C (4-10/m), highlighting a relatively low level of litter presence. The interaction of human activities, both as inhabitants and visitors, may contribute to fluctuations in water quality. Understanding these dynamics is crucial for sustainable management, ensuring the preservation of Pulau Kelapa's ecological integrity as a cherished marine environment and tourist attraction. This study provides insights into the delicate balance between human interactions and environmental preservation in the context of Pulau Kelapa, Kepualauan Seribu.Keywords:Water qualityLitter DistributionKelapa Dua IslandKepulauan Seribu